The Effect of Financial Literacy, Financial Behavior and Income On Investment Decisions - Muh Asdar; Syamsul Ridjal; Jannati Tangngisalu (Pascasarjana STIE Amkop Makassar, 2022)
AbstractThis study aims to determine the effect of financial literacy, financial behavior and income on investment decisions of active students at the STIEM Bongaya Makassar Investment Gallery. Collecting data using primary data obtained from the questionnaire. The sampling method used is Census sampling. The population in this study were 40 respondents. The results of the questionnaire have been tested for validity and reliability, and classical assumptions have been tested in the form of normality, heteroscedasticity and multicollinearity. Methods of data analysis using descriptive analysis techniques, path analysis and multiple linear regression analysis. Test the data hypothesis using Partial Test (t test) and Determination Test (R2 test) with the help of SPSS software version 23. The results of this study indicate that the variables of Financial Literacy and Financial Behavior have a positive and significant effect on Investment Decisions and Income has no effect on Investment Decisions. The results of this study can also be used for researchers and further researchers as well as parties who need it as a source of reference and information related to this research. Keywords: Financial Literacy, Financial Behavior, Income and Investment Decisions